Interaction of galacto-oligosaccharides and lactulose with dipalmitoylphosphatidilcholine lipid membranes as determined by infrared spectroscopy - Díaz, Sonia Beatriz (2017)
Lactulose and galacto-oligosaccharides (GOS) have been recognized as health promoting compounds due to their recognized prebiotic capacity. In addition, because of their polyhydroxilated nature, they are effective protectants during processes involving dehydration of lactic acid bacteria. The protective effects of sugars have been associated with their capacity to replace water molecules from lipid membranes and/or to form glassy matrices. Although this latter property has been previously investigated for GOS and lactulose, the capacity of these sugars to replace water molecules was not. Furthermore, it must be considered that GOS are usually mixtures of oligo-saccharides with differentdegrees of polymerization (DP) including or excluding different amounts of mono and disaccharides, and the effect of their composition on the GOS-membrane interaction has not been addressed so far. The aim of the present work was to study the interaction of lactulose and GOS of different compositions with dipalmitoylphosphatidilcholine (DPPC) membranes both in the gel (Lb) and in the liquid crystalline phase (La) by using infrared spectroscopy. Both GOS and lactulose interacted with the phosphate groups of the polar head region, but only lactulose (disaccharide) penetrated into the lipid bilayers anddecreased the membrane phase transition (Tm). In contrast, GOS containing no mono and disaccharides were excluded from the hydrophobic region, leading to an increase of the Tm. In turn, GOS containing mono and disaccharides showed a concentration-dependent effect. The results obtained shed light on the mechanisms involved in protection mediated by GOS and lactulose, thus providing support to improve the stabilization of lactic acid bacteria.